BUILDING STUDENT WORK READINESS: THE ROLE OF GOAL ORIENTATION AND VOCATIONAL SCHOOL LEARNING FACILITIES - Fithriyah, Aliffa Nurul; Faslah, Roni; Fidhyallah, Nadya Fadillah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The purpose of this study was to determine the effect of (1) goal orientation on students' work readiness, (2) learning facilities on students' work readiness, and (3) goal orientation and learning facilities on students' work readiness at vocational high schools. This study was conducted using a quantitative approach, with an ex-post facto research type. The population in this study were students of Public Vocational Schools 10 Jakarta who would carry out field work practice. The sample of this study was 140 people. Sampling was carried out using with the proportional random sampling sampling technique. Data collection used a questionnaire. The data analysis technique used was multiple linear regression, using the SPSS 26 statistical application. The results of this study were: (1) goal orientation had an effect on work readiness, (2) learning facilities had an effect on students' work readiness, and (3) goal orientation and learning facilities together had an effect on students' work readiness. From the results of this study, it is suggested that students should better prepare themselves to enter the world of work because of the increasing competition in entering the world of work. Then, improving the quality of facilities and infrastructure and learning processes in schools needs to be considered.Goal orientation